Time course of muscle soreness following different types of exercise - Vickers, A. J. (2001)
BACKGROUND: Post-exercise muscle soreness is a dull, aching sensation that follows unaccustomed muscular exertion. Primarily on the basis of previous laboratory-based research on eccentric exercise, soreness is usually said to follow an inverted U-shaped curve over time, peaking 24 - 48 hours after exercise. As such, it is often described as "delayed-onset" muscle soreness. In a study of long-distance runners, soreness seemed to peak immediately and then reduce gradually over time. The study is a secondary analysis of clinical trial data that aims to determine whether the time course of soreness following a natural exercise, long-distance running, is different from that following a laboratory-based exercise, bench-stepping. METHODS: This is a reanalysis of data from three previous clinical trials. The trials included 400 runners taking part in long-distance races and 82 untrained volunteers performing a bench-stepping test. Subjects completed a Likert scale of muscle soreness every morning and evening for the five days following their exercise. RESULTS: Interaction between trial and time is highly significant, suggesting a different time course of soreness following running and bench-stepping. 45% of subjects in the bench-stepping trial experienced peak soreness at the third or fourth follow-up (approximately 36 - 48 hours after exercise) compared to only 14% of those in the running trial. The difference between groups is robust to multivariate analysis incorporating possible confounding variables. CONCLUSION: Soreness in runners following long-distance running follows a different time course to that in untrained individuals undertaking bench-stepping. Research on exercise taking place in the laboratory context does not necessarily generalize to exercise undertaken by trained athletes when engaged in their chosen sport. BMC Musculoskelet Disord 2001;2(1):5